Guidelines for Promoting Happiness from Vipassana Meditation Practitioners of the Vipassanathura Institute at Mahachulalongkornrajavidyalaya University - Tohthea, Phrabaidika Apichart Abhijāto; Suwanprateep, Thanee (Journal of Dhamma for Life, 2025)
This research aimed to: (1) examine happiness derived from the practice of Vipassanā meditation, (2) study the Vipassanā meditation practices of the Institute of Vipassanā Dhura, Mahachulalongkornrajavidyalaya University, and (3) propose guidelines for promoting happiness through Vipassanā meditation practice at the Institute of Vipassanā Dhura, Mahachulalongkornrajavidyalaya University. The study employed a qualitative research methodology, collecting data through in-depth interviews with purposively selected key informants. The participants consisted of 18 monks/persons categorized into four groups: three administrators of the Institute of Vipassanā Dhura, five Vipassanā meditation teachers, three experts in Vipassanā meditation, and seven meditation practitioners. The research instrument was a semi-structured in-depth interview, and the data were analyzed using descriptive content analysis. The findings revealed that Vipassanā meditation practice is a significant process for enhancing both physical and mental well-being. The happiness derived from the practice can be classified into four levels: happiness from moral discipline (sīla), concentration (samādhi), wisdom (paññā), and liberation (vimutti-sukha), which represents a stable and enduring form of happiness unaffected by worldly conditions. The meditation approach of the Institute emphasizes the practice of the Four Foundations of Mindfulness (satipaṭṭhāna 4), grounded in three essential principles: ardent effort (ātāpī), clear comprehension (sampajañña), and mindfulness (sati). This practice leads to insight into the Three Characteristics of existence: impermanence (anicca), suffering (dukkha), and non-self (anattā). Furthermore, the promotion of happiness through Vipassanā meditation requires supportive internal and external conditions. The knowledge synthesized from this research comprises seven key components: practice based on the Four Foundations of Mindfulness, internal supportive qualities (ātāpī, sampajañña, and sati), external supportive conditions (sappāya 7), principles of spiritual friendship (kalyāṇamittatā 7), the Five Hindrances (nīvaraṇa 5), the Ten Mental Bondages (palibodha 10), and happiness derived from Vipassanā meditation practice. These factors function as essential mechanisms for cultivating wisdom that enables practitioners to perceive mind and body as they truly are, leading to genuine liberation from suffering and sustainable happiness along the path of the Noble Eightfold Path.